Xue-Jie-San restricts ferroptosis in Crohn’s disease via inhibiting FGL1/NF-κB/STAT3 positive feedback loop - Gao, Ying; Zhang, Zhaozheng; Du, Jun; Yang, Xiao; Wang, Xiaopeng; Wen, Ke; Sun, Xueliang (Frontiers in Pharmacology, 2023)
Crohn’s disease (CD) is an incurable inflammatory bowel disease due to unclear etiology and pathogenesis. Accumulating evidences have shown the harmful role of ferroptosis in CD onset and development. Additionally, fibrinogen-like protein 1 (FGL1) has been verified to be a potential therapeutic target of CD. Xue-Jie-San (XJS) is an effective prescription for treating CD. However, its therapeutic mechanism has not been fully elucidated. This study aimed to determine whether XJS alleviating CD via regulating ferroptosis and FGL1 expression. A colitis rat model was induced by 2,4,6-trinitrobenzene sulfonic acid and treated with XJS. The disease activity indices of the colitis rats were scored. Histopathological damage was assessed using HE staining. ELISA was performed to examine inflammatory cytokines. Transmission electron microscopy was utilized to observe ultrastructure changes in intestinal epithelial cells (IECs). Iron load was evaluated by examining iron concentrations, the expressions of FPN, FTH and FTL. Lipid peroxidation was investigated through detecting the levels of ROS, 4-HNE, MDA and PTGS2. Furthermore, the SLC7A11/GSH/GPX4 antioxidant system and FGL1/NF-κB/STAT3 signaling pathway were examined. The results showed that colitis was dramatically ameliorated in the XJS-treated rats as evidenced by relief of clinical symptoms and histopathological damages, downregulation of pro-inflammatory cytokines IL-6, IL-17 and TNF-α, and upregulation of anti-inflammatory cytokine IL-10. Furthermore, XJS administration led to ferroptosis inhibition in IECs by reducing iron overload and lipid peroxidation. Mechanistically, XJS enhanced the SLC7A11/GSH/GPX4 antioxidant system negatively regulated by the FGL1/NF-κB/STAT3 positive feedback loop. In conclusion, XJS might restrain ferroptosis in IECs to ameliorate experimental colitis by inhibition of FGL1/NF-κB/STAT3 positive feedback loop.